The Development of Football Shooting Exercise Using The Back Feet of PS UNDHARI Players - Yhuda Kukuh Prasetia; Muhammad Sukron; Dian Estu Prasetyo (The Future of Education Journal, 2022)
The development model uses the ADDIE model which consists of 5 stages, namely, analysis (analyze), design (design), development (development), implementation (implementation), evaluation (evaluation). The five stages were carried out through material analysis and analysis of student characteristics. Then the validation test by 3 validators, practicality test by PJOK teachers and 10 basketball athletes, after the model is categorized as valid and practical, then the effectiveness test is carried out. The research results of researchers have been tested for validity, practicality and effectiveness. In the validity test conducted by the validator of this model, it obtained an average of 84.48% and was categorized as very valid. the practice of this model was carried out by a feasibility test, 1 teacher obtained a proportion of 92%, was considered very valid and 25 students who made a jump in achievement of 82% were categorized as complete. Based on this explanation, it can be concluded that this model is suitable for use in the long jump learning process at SMPN 02 Tebo Regency